A Glance at the Use of Glucocorticoids in Rare Inflammatory and Autoimmune Diseases: Still an Indispensable Pharmacological Tool? - Ronchetti, Simona; Ayroldi, Emira; Ricci, Erika; Gentili, Marco; Migliorati, Graziella; Riccardi, Carlo (Frontiers in Immunology, 2021)
Since their discovery, glucocorticoids (GCs) have been used to treat almost all autoimmune and chronic inflammatory diseases, as well as allergies and some forms of malignancies, because of their immunosuppressive and anti-inflammatory effects. Although GCs provide only symptomatic relief and do not eliminate the cause of the pathology, in the majority of treatments, GCs frequently cannot be replaced by other classes of drugs. Consequently, long-term treatments cause adverse effects that may, in turn, lead to new pathologies that sometimes require the withdrawal of GC therapy. Therefore, thus far, researchers have focused their efforts on molecules that have the same efficacy as that of GCs but cause fewer adverse effects. To this end, some GC-induced proteins, such as glucocorticoid-induced leucine zipper (GILZ), have been used as drugs in mouse models of inflammatory pathologies. In this review, we focus on some important but rare autoimmune and chronic inflammatory diseases for which the biomedical research investment in new therapies is less likely. Additionally, we and critically evaluate the possibility of treating such diseases with other drugs, either GC-related or unrelated.